Morgan Housel. (2020). The Psychology of Money:Timeless lessons on wealth, greed, and happiness. Harriman House. - Pasztor, Sabrina, K.; Pesuth, Tamas (Public Finance Quarterly, 2024)
Financial “how-to” and “self-help” books have long attempted to reduce complex economic and ﬁnancial terminology to make language and guidance more accessible to an interested reader. A standard approach in the literature is to share speciﬁc linear ﬁnancial steps a reader can pursue while infusing advice with rich narratives, “tell-alls,” and axioms in primarily academic and relatable language. Morgan Housel’s (2020) The Psychology of Money: Timeless Lessons on Wealth, Greed, and Happiness is no exception to this paradigm. It functions as a guide and cautionary tale to the layperson seeking ﬁnancial advice, beginning, and more experienced individual investors who seek a straightforward approach to getting and staying ﬁnancially secure. The text presents a practical framework for wealth accumulation and a series of 19 stories reﬂecting the experiences of well-known public ﬁgures in ﬁnance (think Warren Buﬀet), billionaire entrepreneurs (Walt Disney, Jeﬀ Bezos), cautionary tales (Rajat Gupta, former CEO of McKinsey, Bernie Madoff), staying the course (Livermore and Germansky as 1920s Depression-era stock market operators; Rick Guerin as Buffet’s contemporary whose desire for quick returns led to his downfall), and luck, quipping “you can be wrong half the time and still make a fortune” (p. 67). As an experienced award-winning expert on behavioral finance and former Wall Street Journal columnist, Housel’s goal is to explain basic tenets of investing in an easily digestible format using storytelling and historical data.